Exchanges of innovation resources inside venture capital portfolios - González-Uribe, Juanita (Journal of Financial Economics, 2020)
I explore the prevalence of exchanges of innovation resources inside venture capital portfolios. I show that after companies join investors’ portfolios, several proxies of exchanges between them and portfolio companies (relative to matched nonportfolio companies) increase by an average of 60%. The increase holds when joining events are plausibly exogenous and when VCs’ bargaining power and potential conflicts of interest are low. Three novel mechanisms are supported: carve-outs, spawning, and recycling, whereby entrepreneurs divest innovation units, start new ventures, and reuse assets in other portfolio companies, respectively. Results suggest that returns to innovation are higher in venture capital portfolios.